Anti-Humanism in the Counterculture - Stevenson, Guy. author. aut Link
VII, 223 p.
Keywords: This book offers a radical new reading of the 1950s and 60s American literary counterculture. Associated nostalgically with freedom of expression, romanticism, humanist ideals and progressive politics, the period was steeped too in opposite ideas – ideas that doubted human perfectibility, spurned the majority for a spiritually elect few, and had their roots in earlier politically reactionary avant-gardes. Through case studies of iconic figures in the counterculture – the sexual revolutionary Henry Miller, Beat Generation writers Jack Kerouac, Allen Ginsberg and William S. Burroughs and self-proclaimed ‘philosopher of hip’, Norman Mailer – Guy Stevenson explores a set of paradoxes at its center. Between a Walt Whitman-like optimism and pessimistic modernist intuitions; between brutal rhetoric and emancipatory desires; and between social egalitarianism and spiritual elitism. Such paradoxes, he argues, are vital to an understanding of the cultural and political worlds these writers helped shape – in their time and beyond.